Together for Hope and Resilience: A Humanistic Experience by the Vulnerability, Trauma, Resilience and Culture Lab Members during the COVID-19 Pandemic. Issue 8 (16th November 2020) - Cénat, Jude Mary; Noorishad, Pari-Gole; Blais-Rochette, Camille; McIntee, Sara-Emilie; Mukunzi, Joana N.; Darius, Wina Paul; Broussard, Cathy; Morse, Catherine; Ukwu, Gloria; Auguste, Emmanuelle; Menelas, Kerry
Abstract: The COVID-19 pandemic has brought stress and anxiety to students, professors, and staff in universities. The effectiveness of members of research laboratories not directly involved in research on the virus may be impacted. At the University of Ottawa, laboratories have been affected by the shutdown of all non-essential activities. An experience in a research laboratory at the University of Ottawa observed that members were affected by anxiety, stress, sleep deregulation, etc. However, a humanistic approach that allowed members to share their COVID-19 experiences in an authentic, empathic atmosphere leads them to regain their effectiveness, create hope, and develop resilience strategies.